Citizens' participation in elections in Nigeria: an analysis of the 2011 general elections in Benin City (2015)
Elections are ways by which citizens select their representatives into various elective positions in the state. There are series of activities which citizens take part in; particularly pre-elections activities that facilitate this process of selection. Utilizing the survey method of data gathering, the paper examined the participation of citizens in elections in Nigeria. Using Benin .City as the study area, the research sampled the opinions of citizens regarding their involvement in the 2011 general elections. The study found that citizens' participation in the 2011 elections in Benin City was low. It revealed that political apathy exists among citizens in the political system as the citizens' level of participation in the elections, was restricted to voting alone. The paper also identified some factors that attract and repel citizens as it regards their roles in elections as well as the reasons for political apathy in the 2011 elections in Benin City. The study concludes that citizens' participation in the elections revolves largely around the spectator level.